Patient concerns inventory head and neck as an individualised approach to assess post-treatment outcomes among oral cancer patients in Malaysia / Ainon Natrah Aminnudin - Ainon Natrah, Aminnudin (2020)
Background: Oral cancer and its treatment undisputedly impacts patients‘ quality of life, posing a challenge to clinicians in managing them optimally. Identifying patients‘ concerns is central to holistic patient care; as such time constraints faced by clinicians during consultation sessions may pose a barrier in identifying such concerns effectively. The use of PCI-H&N during post-treatment oral cancer consultation sessions has previously shown to be beneficial, simultaneously promoting effective patient- clinician communication during consultations. Objectives: This study aimed to determine the feasibility of the PCI-H&N in assessing post- treatment oral cancer patients concerns and its relationship with patients‘ HRQoL, psychological distress and satisfaction during their follow-ups consultation. Methods: A mixed mode study design was conducted among post-treatment oral cancer patients in multiple centres of Oral Maxillofacial Surgery Clinics in Malaysia, in two phases; i) Phase I: 3-armed pragmatic RCT among post-treatment oral cancer patients, and ii) Phase II: focus group discussion among health personal. A sample of 123 post-treatment oral cancer patients attending their follow-up reviews were recruited comprising Malaysians aged 18 years and above, completed treatment and on follow-up from one month until five years or more. A set of self-administered questionnaires was administered pre and post-consultation. The primary outcomes were patients‘ HRQoL assessed by the FACT-H&Nv4.0, psychological distress by using Distress Thermometer and satisfaction with the followup consultation measured by a study specific questionnaire. The feasibility and preferred versions of PCI-H&N were secondary outcomes assessed with specific questionnaires respectively. The data were analysed descriptively; multiple linear regression and multivariate logistic regression analyses were used to determine possible predictors of patients‘ HRQoL and psychological distress. Results: Response rate was 88% with 63% patients completing the post-consultation questionnaires. The median iv (IQR) number of the PCI-H&N items selected was three (1-5.5) and 43.5% patients selected four or more concerns. ‗Recurrence or fear of cancer coming back‘ (31.8%) was most frequently selected. A shorter time was taken by patients to complete the paper version (4.0 + 3.7 mins; 95% CI: 3.87, 5.87) than the computerised web-based version (6.0 + 4.5 mins; 95% CI: 5.55, 8.92). A high number of concerns was strongly significant among patients of ‗one-month to one-year post-treatment‘ (n=84%) (p=0.001). Significant association existed between ‗time after treatment completed‘ and concerns of ‗chewing/eating‘, ‗mouth opening‘, ‗swelling‘, ‗weight‘,‘ ability to perform‘, ‗cancer treatment‘ and ‗supplement/ diet-related‘. ‗Chewing/eating‘ scored highly for predicting low HRQoL (p< 0.0001) followed by ‗appearance‘ and ‗ability to perform recreation activities‘ (personal function domain). Patients at risk of psychological distress were 14 times more likely to select ‗ability to perform recreation activities‘ and 7 times more likely to select ‗feeling depressed‘. No significant association was identified between patients satisfaction with the consultation and patients concerns. Conclusion: The use of PCI-H&N as an individualised approach during follow-up consultations could potentially enhance patient-centred care by improving doctor-patient communication, identifying oral cancer patients' concerns and further improving quality care delivery for Malaysian oral cancer patients. In addition, the computerized web-based version is in tandem with patient health management system advancement. Keywords: Patient Concerns Inventory (PCI), health-related quality of life, psychological distress, oral cancer and paper version.